Interferometric measurement of the density of aqueous solutions under ultra-high hydrostatic pressure - Interferometrische Messung der Dichte wässriger Lösungen unter Ultrahochdruck - Eder, Cornelia; Delgado, Antonio (Technisches Messen, 2007)
This contribution describes a densitometer that is based on a Jamin interferometer. It allows the investigation of transparent liquids at a pressure up to 5000 bar. The precision is better than 0.3%. Besides the investigation of the pressure dependence of density and compressibility of aqueous solutions these high precision measurements facilitate the calculation of the partial molar volumes of the solids and thus conclusions concerning the formed hydration shells.
UnivIS-Import:2015-03-09:Pub.2007.tech.ITC.stmmec.interf
Keywords: density measurement; high pressure; Jamin interferometer; aqueous solutions